Extending the measurement temperature range in a fully automated luminescence reader to −50 °C. (May 2019) - Discher, Michael; Dornich, Kay; Richter, Andreas; Mauz, Barbara; Lang, Andreas
Abstract: It is today well established that the luminescence signal is temperature-dependent with compelling evidence provided for temperatures above room temperature. For the signal temperature dependence on lower temperatures, however, our knowledge is rather limited due to the lack of luminescence readers that allow cooling as well as heating in an automated setup. Here, we present technical details and test results of an upgraded Lexsyg Research luminescence reader equipped with a thermoelectric cooling device: a Peltier element. It allows cooling and heating a sample between −50 °C and 100 °C. The measurement chamber of the Lexsyg reader is equipped with a rotating arm to move aliquots between irradiation and readout position. For heating beyond 100 °C the sample is transported to the standard heating element of the reader. Performance tests of the developed cooling unit show that the samples can be held at temperatures below freezing (−40 °C) for more than 1 h and that the reproducibility of cooling and heating cycles is excellent. The new cooling unit enables irradiation and luminescence measurements below ambient temperatures in a fully automated setup. Highlights: A novel cooling unit was developed for a Lexsyg Research unit. Cooling unit enables cooling and heating a sample between −50 °C and 100 °C. Performance tests show excellent reproducibility of pre-defined temperature-time curves for cooling and heating. Irradiation and luminescence measurements are possible to be performed below ambient temperatures in a fully automated setup.